An analytical study of the Meranao political culture in Lanao Del Sur, Philippines - Cayamodin, Jamel Rombo (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The Muslims in the Philippines are currently facing a robust political dilemma that brought malevolent impacts to the people and their societies. This phenomenon made Muslim provinces including those inhabited by Meranaos as the country's most politically desperate and economically backward provinces. The main objective of this study is to analyse the nature of Meranao political culture in the province of Lanao del Sur, Philippines. It examines the major dimensions of political culture in order to determine how politics affects Meranaos and their ailing society. The study adopted both quantitative and qualitative approaches. On one hand, survey method was used in collecting relevant data. There were 315 respondents who took part in the survey. These respondents represent different classes and statuses in the social stratification of the Meranao society. On the other hand, a set of open-ended questionnaires was formulated in order to indulge the qualitative approach adopted in this study. This questionnaire was used for personal interviews with 6 selected scholars and experts who have irrefutable authority to talk about the topic under study. The collection of data was conducted in five-month period from March to July in the year 2012. The study found that the Meranaos have “Subject Political Culture”. People are seen to be related only to the political system as a whole, which is regarded as passive relationship. It was found that Meranaos are not keen to participate in both transitional and gladiatorial levels of political activities. Our general analysis suggests that they are only confined with spectatorial level of political activities that are believed to have only minimal influence on political processes. The respondents' level of political efficacy, though it was found slightly high, was not able to encourage respondents to participate in transitional and gladiatorial political activities. This scenario, as further unveiled by our findings, is due to the higher feelings of cynicism of the Meranaos towards their political system. In sum, political dilemma occurs in Lanao del Sur mainly because of certain political attitudes of the Meranaos which are below par.